Assessment of the correlation between arterial blood gas indices and duration of stay in the emergency department observation unit for pediatric patients aged 0-18 with rotavirus gastroenteritis (Annals of Medical Research, 2024)
Aim: Rotavirus (RV) is the predominant pathogen responsible for the onset of infectious acute gastroenteritis among children younger than five years of age, which is one of the critical public health concerns and one of the childhood gastroenteritis that can cause morbidity and mortality. Although definitive diagnostic methods are essential in such cases, these methods are not always easily accessible. That study aims to investigate the association between blood gas parameters in respondents who have tested positive for RV antigen and their subsequent observation time in the emergency department, as well as the length of their hospitalization.Materials and Methods: This retrospective analysis encompassed 237 individuals ranging from 0 to 18 years old who sought medical attention at the outpatient clinic or emergency department of Adıyaman University Faculty of Medicine Training and Research Hospital and were found to have a positive RV antigen test. Respondents were segregated into cohorts according to age, gender, blood gas parameters, hemogram, biochemical parameters, duration of stay in the emergency observation room, and duration of stay in the pediatric ward. The respondents were categorized based on various criteria, including age, sex, blood gas readings, complete blood count, biochemical markers, duration of stay in the emergency observation area, and hospitalization period in the pediatric unit. Comprehensive demographic, blood gas, hematologic, and biochemical data were compiled and analyzed employing SPSS version 22.0.Results: The study identified significant differences in the participants' pH, pO2, and HCO3 levels, along with the mean platelet volume (MPV). Notably, a significant correlation was established between the pH levels of blood gases in the emergency room observation space and the observation span for respondents testing positive for RV. In contrast, no significant link was observed between blood gas values and the duration of hospital stay. Conclusion: The findings suggest that while blood gas analysis outcomes may not predict hospitalization length in cases of Rotavirus gastroenteritis, respondents presenting with lower blood pH levels tend to spend less time in the emergency observation unit. Therefore, it is recommended that blood gas analysis be conducted routinely for respondents presenting with symptoms of Rotavirus gastroenteritis upon their arrival at the emergency medical services.
Keywords: Rotavirus; Arterial blood gas testing; Gastrointestinal infection; Pediatric health